Gamma Dosimetric Response of Sandalfix Golden Yellow CRL Dye Solutions for Gamma Dosimetry Using Cs137 in the Range 0-1KGy - Muhammad Yousuf Hussain; Taqmeem Hussain; Irfan Toqeer; Nasim Akhtar; Inam-ul-Haq; Hashim Farooq (Journal of Basic & Applied Sciences, 2021)
The effect of gamma radiation source (Cs137) on the aqueous solutions of the Sandalfix Golden Yellow CRLdye was determined in the range 0-1kGy. ?max of the dye was determined by UV/VIS spectrophotometer before the exposure of gamma radiations and was found to be 422 nm. Absorbance of the sample solutions was studied at ?max of the dye at pre and post irradiation. It was determined that the Absorbance of the sample solutions was decreased with increasing absorbed dose. The exposed dye solutions were found to be discolored due to the structural changes in the dye solutions and the discoloration of the dye was found linear with respect to absorbed dose.